Accès aux services de santé et aux services sociaux pour les communautés anglophones en situation minoritaire du Québec : Défis récents, contexte législatif et recommandations de recherche - Shoumarova, Lina (Quebec English-speaking Communities Research Network (QUESCREN), 2024)
Le présent mémoire offre des observations préliminaires sur les recherches existantes concernant l’accès aux services de santé et sociaux pour la communauté anglophone de langue officielle en situation minoritaire au Québec. Il identifie des thèmes et des besoins de recherche. Le mémoire fait également une recommandation sur des mesures qui renforceraient l’écosystème de recherche et soutiendraient ainsi les travaux dans le domaine. Ce mémoire répond donc à la priorité G – « le besoin de recherche, de preuves et de solutions pour soutenir l’accès aux soins de santé dans la langue choisie » – décrite dans le document préparatoire de l’étude du Comité permanent mentionnée ci-dessus
Keywords: Official Language Minority Community (OLMC)

Access to Health and Social Services for Quebec’s English-Speaking Minority Communities: Recent Challenges, Legislative Context, and Research Recommendations - Shoumarova, Lina (Quebec English-Speaking Communities Research Network (QUESCREN), 2024)
This brief offers preliminary observations about existing research on access to health and social services for Quebec’s English-speaking official language minority community (OLMC). It identifies research themes and needs. The brief also makes a recommendation for measures that would strengthen the research ecosystem and thus support work in the field. As such, this brief addresses Priority G – “the need for research, evidence, and solutions to support health care access in one’s chosen language” – outlined in the preparatory document for the Standing Committee’s study mentioned above.
Keywords: Official Language Minority Community (OLMC)

Access to Health and Social Services for Quebec’s English-speaking Minority Communities: Recent Challenges, Legislative Context, and Research Recommendations - Shoumarova, Lina (Quebec English-speaking Communities Research Network (QUESCREN), 2024)
This brief offers preliminary observations about existing research on access to health and social services for Quebec’s English-speaking official language minority community (OLMC). It identifies research themes and needs. The brief also makes a recommendation for measures that would strengthen the research ecosystem and thus support work in the field. As such, this brief addresses Priority G – “the need for research, evidence, and solutions to support health care access in one’s chosen language” – outlined in the preparatory document for the Standing Committee’s study mentioned above.

New Language Directives in Health a Welcome, Significant Step, QCGN Says - Quebec Community Groups Network (QCGN) (2024)

Selon le QCGN, les nouvelles directives linguistiques dans le domaine de la santé sont une étape importante et positive - Quebec Community Groups Network (QCGN) (2024)

Le QCGN se dit heureux de l’adoption de la motion visant à supprimer le certificat d’identité permettant d’avoir accès aux soins de santé - Quebec Community Groups Network (QCGN) (2024)

QCGN Pleased by Motion To Nix Identity Certificate for Health Care - Quebec Community Groups Network (QCGN) (2024)

Le risque de suicide pour la population québécoise d'expression anglaise - Community Health and Social Services Network (CHSSN) (2024)

Suicide Risk for Quebec’s English-speaking Population - Community Health and Social Services Network (CHSSN) (2024)

Adaptation Initiative Project Guide : 2023-2028 - Community Health and Social Services Network (CHSSN) (2024)
This guide to the CHSSN Adaptation Projects 2023– 2028 gives the descriptions of the projects being carried out by our public partners to improve access to health services across the province. These projects take into account the diverse regional realities of the English-speaking communities and are designed to have a direct impact on the ability of an Englishspeaking client to access services in English. Each region develops a project that will advance their capacities to understand the needs of the community and better respond to them. The primary objectives of this program are to 1) improve access to health and social services in English in all regions and 2) support better communication and partnerships between the English-speaking community and public health establishments.

L'initiative d'adaptation guide de projets : 2023-2028 - Community Health and Social Services Network (CHSSN) (2024)
Le présent guide des projets d’adaptation 2023 – 2028 du Réseau communautaire de santé et de services sociaux (RCSSS/ CHSSN) décrit les projets menés par nos partenaires publics en ce qui concerne l’amélioration de l’accès aux services de santé partout dans la province. Ces projets tiennent compte des différentes réalités régionales des communautés d’expression anglaise et sont pensés de façon à avoir un effet direct sur l’accès aux services en anglais pour la clientèle d’expression anglaise. Chaque région élabore son propre projet pour mieux comprendre les besoins de la communauté et mieux y répondre. Les objectifs principaux du programme sont 1) d’améliorer l’accès aux services de santé et aux services sociaux en anglais dans toutes les régions et 2) de cultiver une meilleure communication et de bons partenariats entre la communauté d’expression anglaise et les établissements de santé publique.

Health Directives Should Be Scrapped, Not Tweaked, QCGN Says - Quebec Community Groups Network (QCGN) (2024)

Les directives sur la santé devraient être abandonnées et non ajustées, selon le QCGN - Quebec Community Groups Network (QCGN) (2024)

OQLF Has No Business in Quebec Operating Rooms, QCGN Says - Quebec Community Groups Network (QCGN) (2024)

Selon le QCGN, l'OQLF n'a rien à faire dans les salles d'opération du Québec - Quebec Community Groups Network (QCGN) (2024)

L'accès en anglais aux services de santé et aux services sociaux au Québec : Rapport comparatif 2019-2023 - CROP (2024)

English-language Health and Social Services Access in Québec : Comparison 2019-2023 - CROP (2024)

Brief for Consultations with the Secrétariat aux relations avec les Québécois d’expression anglaise - Seniors Action Quebec (SAQ) (2024)

Communauté du CHSSN Netlink - Community Health and Social Services Network (CHSSN) (2024)

Community Netlink - Community Health and Social Services Network (CHSSN) (2024)

Searching for a Work-Life Balance in Your Health and Social Services Career? - Townshippers' Association; Dialogue McGill (2024)